THE RELATIONSHIP OF MOTIVATION AND PHYSICS LEARNING OUTCOMES USING THE LEARNING CYCLE 5E MODEL - Rini, Endah Febri Setiya; Oktavia, Widia Dina; Hong, Dong Han (EduFisika: Jurnal Pendidikan Fisika, 2024)
Motivation to learn is an important point that students must have so that learning becomes enjoyable. This research aims to determine the relationship between learning motivation and physics learning outcomes after using the 5E learning cycle model. The type of research used is quantitative research. The sample for this research was students of class XI Science from one of the high schools in Jambi City. Data collection techniques include learning motivation questionnaires and test instruments regarding temperature and heat. The data analysis technique in this research uses the IBM SPSS Version 22 application. Based on the results of data analysis in this study, the significance value between learning motivation and student learning outcomes was obtained, namely 0.002, where 0.002 < 0.05, so it can be stated that Ho is rejected and there is a relationship between Learning Motivation and Student Learning Outcomes in Physics learning. The conclusion from the results of this research is that there is a relationship between motivation and students' physics learning outcomes after the teacher uses the 5E learning cycle model.